Development of Media E-Comics Mathematics-Based Problem-Based Learning to Improve Problem-Solving Skills - Irmaya, Nia (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
According to the initial observation in SMP Muhammadiyah 16 Lubuk Pakam, there are educators who have not fully exploited the design, development, and utilization of media, particularly e-comics media that have never been implemented. Additionally, pupils who are still lacking in problem-solving abilities. (1) Creating legitimate, workable, and effective e-comics medium is the goal of this project, and (2) to evaluate the enhancement of problem-solving abilities through the use of e-comics media that are PBL. The ADDIE model was implemented in this investigation. Seventh-grade pupils from SMP Muhammadiyah 16 Lubuk Pakam participated in this investigation. Instrument utilized in the development of e-comics media, including lesson plans, LKPD, and problem-solving ability assessments. The study's findings indicate that the media e-comics satisfy the valid criteria with a score of 4.69, subsequently conducted trials to develop a practical and effective media that satisfies the practical criteria with a score of 88.95, and satisfy the effective criteria with a score of 87.79On average, the N-gain for the medium group was 0.33 when the problem-solving ability was assessed from N-gain to the development trials. In the high category, the average N-gain was 0.73 when the problem-solving ability was measured against posttest I and posstest II. The e-comic media PBL is capable of enhancing the problem-solving abilities of students at SMP Muhammadiyah 16 Lubuk Pakam, as indicated by the N-gain results.